Investigation of a Novel Hepatitis B Virus Surface Antigen (HBsAg) Escape Mutant Affecting Immunogenicity - Hossain, Md. Golzar (PLoS One, 2017)
Mutation in the hepatitis B virus surface antigen (HBsAg) may affect the efficiency of diagnostic immunoassays or success of vaccinations using HBsAg. Thus, antigenicity and immunogenicity analyses of the mutated HBsAg are necessary to develop novel diagnostic tools and efficient vaccinations. Here, the in vitro antigenicity of three wild-type HBsAg open reading frames (ORFs) (adr4, W1S [subtype adr] and W3S [subtype adr]) isolated from clinically infected patients and nineteen synthesized single/double/multiple amino acid-substituted mutants were tested with commercial ELISA kits. Immunofluorescence staining of transfected cells and Western blot analysis confirmed that these ORFs were expressed at comparable levels in HEK-293 cells. W1S and adr4 were clearly detected, whereas W3S could not be detected. Using the same commercial immunoassay kit, we found that the single mutants, K120P and D123T, were marginally reactive, whereas W3S-aW1S and the double mutant, K120P/D123T, exhibited antigenicity roughly equivalent to the wild-type wako1S. On the other hand, the single mutants of W1S, P120K and T123D, significantly impaired the reactivity, while W1S-aW3S and the double mutant of W1S, P120K/T123D, resulted in a complete loss of antigenicity. In addition, ELISA revealed reduced HBs antigenicity of two mutants, W1S N146G and W1S Q129R/G145R. These commercial ELISA-based antigenic reactivities of HBsAg were also strongly correlated with the predicted Ai alterations of affected amino acids due to the specific mutation. In conclusion, this study showed for the first time that lysine (K120) and aspartate (D123) simultaneously affected HBsAg antigenicity, leading to diagnostic failure. These findings will improve diagnostic assays and vaccine development.